Network Relationships for Firm’s Value-Added Strategies: A Case Study of Sarawak Convention Bureau (SCB) - Hamrila, Abdul Latip; Smyrnios, Kosmas X. (Billion Brains, 2012)
The fragmented nature of the convention industry requires a substantial degree of networking and collaboration among the multifaceted network relationships in destination marketing. Forming specific societal structures and processes within the delegates and convention-related businesses, the evolution and progression in convention industry are associated with social benefits through an exchange of ideas, fostering business contacts and facilitating knowledge transfer. These cooperation and collaboration lead to the quest for value-added strategies. Based upon a case study of Sarawak Convention Bureau, this paper proposes a more integrative theoretical framework in an attempt to describe and explain the nature of network relationships in convention industry, and the value-added strategies from the viewpoint of social capital. The case study involves face-to-face interviews, data coding, causal network modelling, and within-case analysis, throughout the interactive processes of qualitative inquiry.